2021
DOI: 10.3390/cancers13236028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Central Compartment Lymph Node Metastases in Papillary Thyroid Micro-Carcinoma: A Retrospective Evaluation of Predictive Preoperative Features

Abstract: Papillary thyroid micro-carcinomas are considered relatively indolent carcinomas, often occult and incidental, with good prognosis and favorable outcomes. Despite these findings, central lymph node metastases are common, and are related to a poor prognosis for the patient. We performed a retrospective analysis on patients treated with surgery for stage pT1a papillary thyroid micro-carcinomas. One hundred ninety-five patients were included in the analyses. The presence of central lymph node metastases was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…In this series of patients, only temporary hypoparathyroidism and vocal cord paralysis were documented, without any permanent occurrence, which could be attributed to the fact that experienced senior surgeons performed all the procedures. Moreover, pCCLND could be considered for patients with cN0 PTC, especially with the help of CNP, as this procedure could be considered relatively safe [ 15 ], and more than a quarter of lymph nodes harvested from the central compartment were metastatic. In fact, central compartment lymph node metastases (CCLNM) are common (20 %–90 %) and are related to a poor prognosis (including recurrence, distant metastases, reduced survival, and higher morbidity), even for patients with cN0 micro-PTC, despite negative preoperative imaging evaluation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this series of patients, only temporary hypoparathyroidism and vocal cord paralysis were documented, without any permanent occurrence, which could be attributed to the fact that experienced senior surgeons performed all the procedures. Moreover, pCCLND could be considered for patients with cN0 PTC, especially with the help of CNP, as this procedure could be considered relatively safe [ 15 ], and more than a quarter of lymph nodes harvested from the central compartment were metastatic. In fact, central compartment lymph node metastases (CCLNM) are common (20 %–90 %) and are related to a poor prognosis (including recurrence, distant metastases, reduced survival, and higher morbidity), even for patients with cN0 micro-PTC, despite negative preoperative imaging evaluation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pCCLND could be considered for patients with cN0 PTC, especially with the help of CNP, as this procedure could be considered relatively safe [ 15 ], and more than a quarter of lymph nodes harvested from the central compartment were metastatic. In fact, central compartment lymph node metastases (CCLNM) are common (20 %–90 %) and are related to a poor prognosis (including recurrence, distant metastases, reduced survival, and higher morbidity), even for patients with cN0 micro-PTC, despite negative preoperative imaging evaluation [ 15 ]. Unfortunately, the sensitivity of both ultrasound and CT imaging for CCLNM is reported to be 42–47 % [ 16 ]; therefore, more than half of patients might only present cN0, but they are not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For stage pT1α papillary thyroid microcarcinoma, multivariate analyses have demonstrated that younger age, male sex, and subcapsular location of the lesion were predictive factors for central lymph node metastasis[ 82 ].…”
Section: Pre/postoperative Prediction Factors-recurrencementioning
confidence: 99%
“…Papillary thyroid carcinoma itself has relatively indolent biological characteristics and superadd the small tumor burden; PTMC patients usually have a good prognosis after treatment ( 4 ). The 2022 National Comprehensive Cancer Network (NCCN) advises against utilizing prophylactic CLND to treat T1 and T2 cN0 PTC ( 5 ).…”
Section: Introductionmentioning
confidence: 99%